The difference of stress distribution of maxillary expansion using rapid maxillary expander (RME) and maxillary skeletal expander (MSE)-a finite element analysis - Nathania Hartono; Benny M. Soegiharto; Retno Widayati (SpringerOpen, 2018)
Abstract Background Maxillary skeletal expander (MSE) in combination with miniscrews was developed to overcome the drawbacks that may have resulted from the application of conventional rapid maxillary expander (RME). This research was conducted to analyze the difference of stress distribution of maxillary expansion using RME and MSE in the region of interests (ROIs): first molars (M1), palatal alveolar bones of M1, palatine sutures, zygomatic sutures, miniscrews, and their surrounding bones. Methods A dry skull was scanned using CBCT and rendered into a three-dimensional (3D) model of craniomaxillary structures. The data analysis was done both visually and numerically. Result The stress distributions in RME group were located at the palatal side of M1, mesial side of palatal alveolar of M1, pulp chamber of M1, and inferior cortex of palatine sutures. The stress distributions in the MSE group were located at the distopalatal cusp of M1, palatal side of palatal alveolar of M1, and inferior and superior cortex of palatine sutures. The stress distributions in zygomatic sutures on both groups were located at the zygomaticotemporal sutures, whereas in the miniscrews, the stress were located at the anterior miniscrews and palatal side of surrounding bones. Conclusions There were significant differences of stress distribution of maxillary expansion measured in the ROIs in the craniomaxillary 3D model using RME and MSE.